If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = -17 + -3y Reorder the terms: 2 + 3y = -17 + -3y Solving 2 + 3y = -17 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 2 + 3y + 3y = -17 + -3y + 3y Combine like terms: 3y + 3y = 6y 2 + 6y = -17 + -3y + 3y Combine like terms: -3y + 3y = 0 2 + 6y = -17 + 0 2 + 6y = -17 Add '-2' to each side of the equation. 2 + -2 + 6y = -17 + -2 Combine like terms: 2 + -2 = 0 0 + 6y = -17 + -2 6y = -17 + -2 Combine like terms: -17 + -2 = -19 6y = -19 Divide each side by '6'. y = -3.166666667 Simplifying y = -3.166666667
| 5x-15=3x-33 | | 11x=8x-8 | | -9x-16=20 | | 5u=4u-8 | | 7(x+1,2)=56,7 | | 4x^3/0.423 | | (4x^3)/(0.65)^2 | | 2(3x)+2(3x+2)=164 | | 5+7x=-2x+41 | | r/2+5r=11 | | 2/3x=10/13 | | 7+x=-3x+55 | | 6m-11.6=4m+8.2 | | 6*(1/7) | | 1.6(2.8)3x=6(4.5)x | | 5/3b=20 | | 6*1/7 | | (3-6i)-(4+5i)-(-5+i)= | | 4x+20=6x+200 | | 4x+9x+7=0 | | 2s=-3 | | X^3+3x^2+2x=504 | | 5x+15=3x-7 | | 15x-6=7x+10 | | y-2/6=y+1/15 | | 2(3x-2)=164 | | 7/10-1/6 | | 344.2x+23.2x+129.32=124.2x-723.2 | | 94.50x1/2 | | 5y-5-4y=7-6 | | 7-b=13 | | 4/7(-2) |